FUNDAMENTALISME DAN KERUKUNAN UMAT BERAGAMA - Risnawaty Sinulingga (STT Amanat Agung, 2014)
This article contains discussion about fundamentalism and its effect in the society. Fundamentalism in religion causes conflict which always endangers Indonesian community. Actually, fundamentalism in religion is not supported by the teaching of mainstream religions. According to the biblical research we have done in the Bible, Christians are ordered to live in harmony with the believers of all religions. In the Old Testament, it is taught that God is the Lord of the whole universe and all believers. Each religion must have its own goodness. Meanwhile in the New Testament, Jesus Christ opposed fundamentalism in religion. He ordered us to love others include believers of other religions.